Implementasi Edukasi Kesehatan sebagai Strategi Pemasaran Produk Probiotik Melalui Media Sosial: Studi Kasus di PT Yakult Indonesia Persada - Mafudah Mafudah; Adelia Rizkia Zalfa; Oktavia Ai Nur Kamaliya; Dian Kusumawati; Reza Abdul Kharis; Sukirman Sukirman (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the implementation of health education as an integrated marketing strategy for probiotic products through social media at PT Yakult Indonesia Persada. Health education is increasingly recognized as a strategic approach in value-based marketing, where companies offer not only products but also knowledge and added value for consumer well-being. The research employed a qualitative descriptive method using field observation, interviews with marketing staff, and a literature review of related studies. The findings indicate that PT Yakult Indonesia Persada successfully incorporates health education into its marketing activities through the Yakult Lady program, school visits, health seminars, factory tours, and interactive digital content on social media platforms. These strategies have proven effective in raising consumer awareness of digestive health, strengthening brand image, and maintaining customer loyalty. The study highlights the crucial role of social media integration in reaching younger demographics, fostering engagement, and amplifying educational messages. The consistent delivery of educational content, supported by visual storytelling and personalized approaches, has contributed significantly to Yakult’s sustainable growth in the Indonesian probiotic market. Theoretically, this study enriches the discourse on digital marketing and health communication, while practically, it offers insights for companies seeking to align promotional strategies with consumer education and public health improvement.